Pertanggungjawaban Pidana terhadap Penyalahgunaan Narkotika yang Dilakukan oleh Anak di Kota Makassar - Zulfauzi, Andi (Sovereign: International Journal of Law, 2023)
This study aims to determine the application of material criminal law as well as legal considerations of judges in making decisions against narcotics abuse by children in Decision Number 96/Pid.Sus-Anak/2017/PN.Mks. The type of research used is empirical legal research which is descriptive qualitative in nature. This research was conducted at the Makassar District Court. The data collection techniques used in this study were interviews, documentation, and literature study. The data analysis technique used is qualitative data analysis techniques. The results showed that the application of material criminal law carried out by the public prosecutor and the panel of judges in making decisions against narcotics abuse by children in Decision Number 96/Pid.Sus-Anak/2017/PN.Mks, basically it’s true. Children who commit crimes of narcotics abuse are expected to continue to receive legal protection in the judicial process for the best interests of the child. Furthermore, cooperation between law enforcement officers, government, social institutions, schools and especially parents is needed in order to prevent narcotics abuse from an early age so that children do not fall into actions that can harm themselves and even destroy their future.